Two new species of an Indian endemic genus Krishnacapritermes Chhotani (Isoptera: Termitidae) from the Kerala part of the Western Ghats, India. (1st October 2020) - Amina, Poovoli; Rajmohana, Keloth; Dinesh, K. P.; Asha, Gopalan; Sinu, Palatty Allesh; Mathew, Jobin
ABSTRACT: Krishnacapritermes Chhotani (Isoptera: Termitidae) is one of the endemic termite genera from the Western Ghats of India. Under the genus, only two species Krishnacapritermes maitii Chhotani and Krishnacapritermes thakuri Chhotani were known earlier. The present study describes two new species, Krishnacapritermes dineshan Amina and Rajmohana sp. nov . and Krishnacapritermes manikandan Amina and Rajmohana sp. nov . from the higher elevation hill ranges of Western Ghats part of Kerala. DNA barcodes based on cytochrome oxidase I genes were generated for K. thakuri and K. dineshan from multiple locations and tested for phylogenetic relationships. The paper provides a dichotomous key for the four species of Krishnacapritermes and a species distribution map, along with data on the extension of distribution range for K. maitii and K. thakuri . Comments on intracolonial variability of the hyaline lateral points or processes of the labrum in soldier caste are included. Pericapritermes travancorensis Mathew and Ipe syn. nov . is treated as a junior synonym of K. thakuri . http://www.zoobank.org/urn:lsid:zoobank.org:pub:E2F050B5-2F85-415A-A446-4DC7FCDA1068